Identification of binding sites contributing to volatile anesthetic effects on GABA type A receptors. Issue 8 (5th March 2018) - Woll, Kellie A.; Zhou, Xiaojuan; Bhanu, Natarajan V.; Garcia, Benjamin A.; Covarrubias, Manuel; Miller, Keith W.; Eckenhoff, Roderic G.
Abstract : Most general anesthetics enhance GABA type A (GABAA ) receptor activity at clinically relevant concentrations. Sites of action of volatile anesthetics on the GABAA receptor remain unknown, whereas sites of action of many intravenous anesthetics have been identified in GABAA receptors by using photolabeling. Here, we used photoactivatable analogs of isoflurane (AziISO) and sevoflurane (AziSEVO) to locate their sites on α1 β3 γ2L and α1 β3 GABAA receptors. As with isoflurane and sevoflurane, AziISO and AziSEVO enhanced the currents elicited by GABA. AziISO and AziSEVO each labeled 10 residues in α1 β3 receptors and 9 and 8 residues, respectively, in α1 β3 γ2L receptors. Photolabeled residues were concentrated in transmembrane domains and located in either subunit interfaces or in the interface between the extracellular domain and the transmembrane domain. The majority of these transmembrane residues were protected from photolabeling with the addition of excess parent anesthetic, which indicated specificity. Binding sites were primarily located within α+/β — and β+/α— subunit interfaces, but residues in the α+/γ— interface were also identified, which provided a basis for differential receptor subtype sensitivity. Isoflurane and sevoflurane did not always share binding sites, which suggests an unexpected degree of selectivity.—Woll, K. A., Zhou, X., Bhanu, N. V., Garcia, B. A., Covarrubias, M., Miller, K. W., Eckenhoff, R. G. Identification of binding sites contributing to volatile anesthetic effects on GABA type A receptors. FASEB J . 32, 4172–4189 (2018). www.fasebj.org